Answer :

Two zeroes are √3 and -√3,


Therefore (x -√3)(x - (-√3) = (x - √3)(x + √3) is a factor of p(x).


Let us divide p(x) by (x - √3)(x + √3) = (x2 - 3)



(2x4 - 3x3 - 5x2 + 9x - 3) = (x2 - 3)(2x2 - 3x + 1)


= (x - √3)(x + √3)(2x2 - 2x - x + 1)


= (x - √3)(x + √3)(2x(x - 1) - 1(x - 1))


= (x - √3)(x + √3)(2x - 1)(x - 1)


Hence,


2x - 1 = 0 or x - 1 = 0


or x = 1


Hence, other two zeroes are or 1.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Heights and Distances-IHeights and Distances-IHeights and Distances-I45 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

When a polynomialRS Aggarwal - Mathematics

Find all the zeroRD Sharma - Mathematics